Specialised generalists? Food web structure of a tropical tachinid‐caterpillar community. Issue 5 (5th June 2017) - Stireman, John O.; Dyer, Lee A.; Greeney, Harold F.
Abstract: Most insect species remain unknown and for most described species, we know nothing about their ecology and interactions. Understanding the structure of species interaction webs can provide insight into geographic patterns and ecological drivers of diversity, the stability of communities, and energy flow through ecological systems. We analysed a tachinid parasitoid‐caterpillar food web from the Ecuadorian Andes based on >70 000 caterpillar collections. Our goals were to assess how host taxon and feeding niche affects parasitism by flies and wasps, evaluate perceptions of broad diet breadth in tachinids, characterise the structure of the food web, and assess how sample size affects inferences about community structure. We found high levels of parasitism (>28%) by tachinid and wasp parasitoids and a rich tachinid community (279 spp.). Concealed caterpillars experienced low parasitism by tachinids and were more likely to be attacked by species with indirect oviposition. Indirect ovipositing tachinids had greater host ranges, but this is confounded with tachinid phylogeny. Caterpillar families exhibited nearly opposite patterns of susceptibility to parasitism by tachinids and wasps. Network metrics indicate that this tachinid‐host community is relatively compartmentalised and nested, and though some taxa display broad host ranges, the network as a whole is moderately specialised due to constrained host ranges of many tachinid species. This study establishes an exemplar tropical tachinid‐host food web, providing insight into the diversity and interactions of these important parasitoids. Additional studies are needed to determine how these interactions vary across environmental and geographic gradients.